Aerosol therapy of equine respiratory disorders - Silva, Miriam Bastos da; Duvidier, Didier H.; Votion, Dominique; Art, Tatiana; Lekeux, Pierre (Brazilian Journal of Veterinary Research and Animal Science, 2001)
Respiratory problems are frequently implicated in horses as a cause of poor sportive performances. The most frequently occurring lower respiratory tract disorders are chronic obstructive pulmonary disease (COPD), inflammatory airway disease and exercise-induced pulmonary haemorrhage (EIPH). Classically, their treatment includes systemic administration of drugs, but aerosol therapy is now known to be a more specific way to treat these disorders. This article describes the equipment and drugs currently available for aerosol therapy in horses.